2014
DOI: 10.9790/0853-131146975
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antibacterial activities of euphorbia heterophylla

Abstract: (100, 50, 25, 12.5, 6.25, and 3.16 mg/ml)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…benghalensis against a standard strain of S. aureus. Previous studies [ 25 , 26 ] showed a similar activity on ethanol leaves extract and solvent fractions of E. heterophylla against S. aureus , P. aeruginosa , E. coli, Streptococcus pneumonia , and K. pneumoniae.…”
Section: Discussionmentioning
confidence: 54%
“…benghalensis against a standard strain of S. aureus. Previous studies [ 25 , 26 ] showed a similar activity on ethanol leaves extract and solvent fractions of E. heterophylla against S. aureus , P. aeruginosa , E. coli, Streptococcus pneumonia , and K. pneumoniae.…”
Section: Discussionmentioning
confidence: 54%
“…This result is not in agreement with the previous studies carried out by Nikunj and Kaushik (2014); Jakhar and Dahiya (2017) and Nazeer (2017) that recorded antibacterial activity with all the crude extracts used in their studies. The variation in results obtained in this study may possibly be due to the solvent used for extraction, geographical location of the plant and the characteristics of the soil as opined by Ughachukwu et al (2014).…”
Section: Discussionmentioning
confidence: 86%
“…The presence of phytochemicals such as saponins, flavonoids, terpenoids, tannins, phenols, alkaloids, steroids and reducing sugars in the whole plant crude extracts of Euphorbia hirta were in agreement with the previous studies by Abalaka et al (2016); Ewansiha et al (2016); Mekam et al (2019); Haleshappa et al (2020); Nirmal et al (2020) and Vadalia et al (2020) but the results disagreed with work of Awomukwu et al (2014) because terpenoids and steroids were absent in the study. The difference in results may possibly be due to the type of solvents used for the extraction and the difference in the geographical location where the plants were collected (Ughachukwu et al, 2014). Abalaka et al (2016) and Oloninefa et al (2018) opined in their previous studies that phytochemicals have antimicrobial effects and as such they can be used for the treatment of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The plant is also used for as a lactogenic agent 4 and for curing gonorrhea 5 . Studies have shown that E. heterophylla exhibits antibacterial activity 6,7 , as well as laxative activity 8 . Indeed in Nigeria, the plant is more popular for its laxative properties than for any other use.…”
Section: Introductionmentioning
confidence: 99%